Integrating learning assessment and supervision in a competency framework for clinical workplace education. (February 2015) - Embo, M.; Driessen, E.; Valcke, M.; van der Vleuten, C.P.M.
Summary Although competency-based education is well established in health care education, research shows that the competencies do not always match the reality of clinical workplaces. Therefore, there is a need to design feasible and evidence-based competency frameworks that fit the workplace reality. This theoretical paper outlines a competency-based framework, designed to facilitate learning, assessment and supervision in clinical workplace education. Integration is the cornerstone of this holistic competency framework.